Percepção ambiental dos servidores públicos e empregados terceirizados de uma Instituição Federal de Ensino Superior - Pires, Suenylse Antunes (2021)
The Public Administration, through its university education institutions, has the potential to promote management guided by environmental responsibility and commitment to social issues, beeing an example to society as a model of environmental management. However, IT requires awareness, sensitiveness and attention of outsourced servers and employees about environmental issues, because this behavior can lead to greater engagement and willingness to change the use and consumption of natural resources and public goods. Therefore, the objective of this research is to evaluate the environmental perception of public servants and outsourced employees of the Federal University of São Carlos, Sorocaba site, regarding to issues related to the rational consumption of natural resources, the disposal of materials and the acquisition of consumer goods and material in common use in the institution. For this purpose, a qualitative and quantitative research was developed, with an exploratory and descriptive character, in which the method used is the case study. The theoretical-conceptual basis was made through the bibliographical review to understand the theory of environmental perception. As a data collection instrument, a questionnaire was used, divided into six sections with open and closed questions with the intention to know the profile of respondents and their perceptions about this topic. The data analysis alowed the stratification of the sample and the results pointed out that the understanding and vision of the environment among the categories analyzed presented distinct ranges between them, with specific variations between education level, age, gender and time of experience in the institution. in addition, contributions were made to the resolution of environmental obstacles faced by the community with suggestions for improvement in infrastructure and especially in waste management. Finally, the study allowed to understand the complex relationship between the subject and its environment, which points in common reflect individual behavior and attitudes from the individual to the collective point, as well as the differentiation and meaning of subgroups between categories.